Catalytic performance of the in situ synthesized palladium–polymer nanocomposite. (13th January 2016) - Choudhary, Meenakshi; Siwal, Samarjeet; Nandi, Debkumar; Mallick, Kaushik
Abstract : Multifunctional catalytic performance of the in situ synthesized polymer supported palladium nanoparticles (Pd NP). Abstract : Polymer encapsulated metallic palladium nanoparticles have been synthesized via the oxidative polymerization route using a di-amino naphthalene monomer and a palladium based metal salt. The resultant composite material was characterized by means of optical and microscopic techniques, which offered the information about the chemical structure of the polymer and also the distribution of the metal particles in the composite material. The palladium nanoparticles were homogeneously dispersed throughout the polymer which produced a uniform metal–polymer composite material. The composite material was successfully used for the hydrogenation reaction of the 4-nitrophenolate ion with the evidence of a proton coupled electron transfer (PCET) reaction mechanism. The palladium–polymer composite material was also used as an iodide sensor for the detection of the iodide ion in the presence of other interfering anionic species.